2018
DOI: 10.3389/fendo.2018.00740
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transcript Profiling for the Detection of Neuroendocrine Tumors: Results of a Large Independent Validation Study

Abstract: Background: Available neuroendocrine biomarkers are considered to have insufficient accuracy to discriminate patients with gastro-entero-pancreatic neuroendocrine tumors (GEP-NETs) from healthy controls. Recent studies have demonstrated a potential role for circulating neuroendocrine specific transcripts analysis—the NETest—as a more accurate biomarker for NETs compared to available biomarkers. This study was initiated to independently validate the discriminative value of the NETest as well as the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 45 publications
5
41
0
2
Order By: Relevance
“…The NETest was 93% positive, whereas single analytes were positive in ∼40%. In 2 other independent studies, a daily clinical practice registry audit (NCT02270567) of NEN [102] and a prospective, university-based study [100] the diagnostic accuracy of the NETest was confirmed to be 95-100%. Physician confidence in using monoanalytes like CgA or pancreastatin was low (accuracy 25-50%).…”
Section: T -Primary Tumourmentioning
confidence: 91%
See 1 more Smart Citation
“…The NETest was 93% positive, whereas single analytes were positive in ∼40%. In 2 other independent studies, a daily clinical practice registry audit (NCT02270567) of NEN [102] and a prospective, university-based study [100] the diagnostic accuracy of the NETest was confirmed to be 95-100%. Physician confidence in using monoanalytes like CgA or pancreastatin was low (accuracy 25-50%).…”
Section: T -Primary Tumourmentioning
confidence: 91%
“…The values are standardised, reproducible and are not influenced by age, gender, ethnicity, fasting or acid suppressive medication [98,99]. The assay has been independently validated [100]. Since the multigene assay captures diverse functional "omic" components of each tumour, the assay provides a broad molecular biological characterisation of tumour behaviour.…”
Section: T -Primary Tumourmentioning
confidence: 99%
“…Gene expression data are used in the calculation of the NETest score, ranging from 0 to 100 that reflects disease activity. The ULN is 20 [20], scores of 20-40 are associated with low disease activity, 41-79 represent intermediate disease activity and ≥80 reflect high disease activity ( Fig. 1a) [17].…”
Section: Patient Demographics and Follow-upmentioning
confidence: 99%
“…42,43 The NETest™ has also been reported to be able to differentiate stable from progressive sporadic gastro-pancreatic NETs and may have the potential to predict prognosis 44 42,43 The NETest™ has also been reported to be able to differentiate stable from progressive sporadic gastro-pancreatic NETs and may have the potential to predict prognosis 44 …”
Section: How Us Eful Are Current B I Omark Er S At Pred Ic Ting Thementioning
confidence: 99%
“…Recently, the NETest™, a multitranscript molecular signature for PCR-based blood analysis, has been developed as a biomarker with independent studies reporting variable diagnostic performance in its ability to detect sporadic gastro-pancreatic NETs. 42,43 The NETest™ has also been reported to be able to differentiate stable from progressive sporadic gastro-pancreatic NETs and may have the potential to predict prognosis 44 ; however, additional studies are required to truly establish the clinical utility of the NETest™ in the non-MEN-1 setting. To date, in patients with MEN-1, there are no published data regarding the performance of the NETest™ in the context of MEN1-associated NF-pNETs.…”
Section: How Us Eful Are Current B I Omark Er S At Pred Ic Ting Thementioning
confidence: 99%